Metal heat treatment process

By using water-based quenching liquid prepared with polyether compositions of different molecular weights, the problems of insufficient cooling speed control and excessive viscosity of the water-based quenching liquid are solved, stable cooling and high-quality quenching of the steel structure are achieved, and quenching cracking and Corrosion improves the overall performance of steel.

CN119120846APending Publication Date: 2024-12-13YANGZHOU HENGZHONG PRECISION MASCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411224835.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The insufficient cooling speed control of the water-based quenching liquid during cooling process can easily lead to quenching and cracking of steel structures. Ultra-high molecular weight polymers lead to large viscosity and large fluctuations in cooling parameters, making it difficult to effectively apply to the heat treatment of large steel structures.

Method used

The water-based quenching liquid composition consisting of two polyethers of different molecular weights combined with other additives is prepared by emulsion polymerization and high-pressure reaction. The viscosity and cooling speed of the quenching liquid are adjusted to avoid the low temperature cooling speed too fast, and ensure that The high and low temperatures are moderately cold.

Benefits of technology

It effectively avoids quenching and cracking problems, improves the hardenability of steel, avoids corrosion caused by inorganic precipitation and waste caused by excessive viscosity, improves the quality of workpieces, controls fluctuations in cooling speed, and ensures the large steel structure. stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005024130840000021
    Figure BDA0005024130840000021
  • Figure BDA0005024130840000041
    Figure BDA0005024130840000041
  • Figure FDA0005024130830000011
    Figure FDA0005024130830000011
Patent Text Reader

Abstract

The invention relates to a metal heat treatment process which comprises the following steps: 1) heating a steel sample blank to 900-1000 DEG C, and preserving heat for 2-4 hours to realize austenitization; 2) putting into a quenching system which takes a water-based quenching liquid solution with the mass concentration of 10-20% as a quenching medium for quenching treatment; 3) cooling to room temperature, cleaning the quenched part with clear water, tempering at 590-610 DEG C, and keeping the temperature for 2-4 hours; (4) the steel sample blank is taken out and air-cooled to the room temperature; wherein the water-based quenching liquid solution is prepared from a water-based quenching liquid composition and comprises the following components: polyether A, polyether B, a bactericide, an antirust agent, a defoaming agent and water. According to the heat treatment process, the water-based quenching liquid serves as a quenching medium, the quenching medium combines the characteristics of water and oil, the hardenability of the steel can be improved, quenching cracking deformation is avoided, and the quality of a workpiece product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment, in particular to a metal heat treatment process. Background Art

[0002] Quenching is a heat treatment process for metals and one of the key steps to improve the comprehensive performance of steel materials. Quenching medium is an indispensable and important component in the quenching process. The traditional quenching medium is mainly quenching oil. In order to correspond to the concept of sustainable development, quenching liquids that use "water instead of oil" have become the mainstream of the market. Quenching liquids are mainly a combination of water and polymer compounds. Polymer compounds are deposited on the metal surface to form a thin film to solve the problems of fast cooling speed and easy brittle cracking of water.

[0003] However, water-based quenching fluid has a relatively high cooling rate during the entire cooling process, and there is a problem of insufficient cooling rate control. Usually, it is easy to have a situation where the high-temperature cooling rate is properly controlled but the cooling rate is too fast at low temperatures. For large steel structures, it is easy to form surface sudden cooling, insufficient internal stress and quenching cracking. In addition, the use of ultra-high molecular weight polymers can easily lead to problems such as high viscosity and large fluctuations in cooling parameters. The rational application of water-based quenching fluids in quenching heat treatment processes remains a challenge. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention proposes a heat treatment process using a water-based quenching liquid as a medium. The water-based quenching liquid is a water-based quenching liquid composition composed of two polyethers with different molecular weights combined with other additives. The cooling parameter fluctuation is small, and the cooling rate at high and low temperatures can be maintained at a moderate level, thereby avoiding the problem of quenching cracks in steel structures caused by excessively fast cooling rates at low temperatures.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A metal heat treatment process comprises the following steps:

[0007] 1) Heat the steel sample to 900-1000℃ and keep it warm for 2-4h to achieve austenitization;

[0008] 2) Putting into a quenching system with a water-based quenching liquid solution of 20-30% mass concentration as the quenching medium for quenching treatment;

[0009] 3) Cool to room temperature, wash the quenched parts with clean water, and then temper them at 590-610℃ for 2-4h;

[0010] 4) Take out the steel sample and air cool it to room temperature;

[0011] The water-based quenching liquid solution is prepared from a water-based quenching liquid composition, including the following components:

[0012]

[0013] Wherein, the polyether A is prepared by emulsion polymerization of allyl polyoxyethylene ether with styrene, acrylic acid and acrylamide;

[0014] The polyether B is prepared by polymerizing hydroxyethyl cellulose with diethanolamine as an initiator, and then reacting with ethylene oxide and propylene oxide in the presence of a catalyst to obtain a cellulose-based block polyether.

[0015] Furthermore, the preparation process of the polyether A is as follows:

[0016] S1. Add allyl polyoxyethylene ether, styrene, acrylic acid and acrylamide into a reaction bottle and stir and mix evenly at room temperature;

[0017] S2, prepare an emulsifier aqueous solution, then add it to the reaction bottle in step S1, stir evenly and heat to 70-80°C;

[0018] S3, prepare an initiator aqueous solution, add it dropwise into the reaction bottle of step S2 during stirring, continue the reaction for 3-5 hours, and discharge the material after cooling.

[0019] Furthermore, the molar ratio of the allyl polyoxyethylene ether to styrene, acrylic acid and acrylamide is 1:80-100:20-40:10-20; the molecular weight of the allyl polyoxyethylene ether is 1000-2400; the amount of the emulsifier and the initiator are 2% and 0.5-2% of the total mass of the monomers, respectively.

[0020] Furthermore, the emulsifier aqueous solution is prepared from sodium dodecylbenzene sulfonate and water; the initiator aqueous solution is prepared from potassium persulfate or ammonium persulfate and water.

[0021] Furthermore, the preparation process of the polyether B is as follows:

[0022] 1) Hydroxyethyl cellulose is dissolved in DMSO, and then five times the amount of dichlorothionyl is added, and stirred at 60-80°C to obtain chlorohydroxyethyl cellulose; then it is redissolved in DMSO, 10 times the amount of diethanolamine is added, and the reaction is carried out at 80-100°C overnight to obtain diethanolamine cellulose;

[0023] 2) The prepared diethanolamine cellulose is put into a high-pressure reactor, a sodium methoxide methanol solution is added as a catalyst, and polymerization reaction is carried out with propylene oxide and ethylene oxide in sequence at 100-140° C. to prepare a cellulose-based block polyether.

[0024] Furthermore, the mass ratio of the diethanolamine cellulose, propylene oxide and ethylene oxide is 0.05:3 to 5:1.

[0025] Furthermore, the fungicide is triazine, methylenebismorpholine or dimethyloxazolidine.

[0026] Furthermore, the rust inhibitor is selected from one of boric acid, boric acid esters, and isononylaminocaproic acid.

[0027] Furthermore, the defoaming agent is a silicon defoaming agent.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the heat treatment process provided by the present invention uses a water-based quenching liquid as a quenching medium, and the quenching medium combines the characteristics of water and oil, can improve the hardenability of steel, and avoid quenching cracking and deformation. The quenching liquid composition of the present invention is mainly a medium-high molecular weight polyether composition, supplemented by a rust inhibitor, a bactericide, and a defoamer. The water-based quenching liquid prepared by adding water has simple ingredients and does not contain inorganic salts or ultra-high molecular weight organic matter, thereby avoiding the problems of inorganic matter precipitation causing corrosion of the steel structure surface during quenching and excessive viscosity adsorbed on the steel structure surface causing waste; polyether A and polyether B cooperate with each other, and the synergistic effect effectively adjusts the viscosity of the quenching liquid, thereby achieving the purpose of controlling the cooling rate, and the fluctuation of the cooling rate parameter is small, which overcomes the problem of quenching cracking caused by insufficient internal stress of the workpiece after quenching; the compatibility of the remaining additives when mixed with the polyether composition is good, thereby improving the quality of the workpiece product. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] Embodiment: A metal heat treatment process comprises the following steps:

[0032] 1) Heat the steel sample to 900-1000℃ and keep it warm for 2-4h to achieve austenitization;

[0033] 2) Putting into a quenching system with a water-based quenching liquid solution of 20-30% mass concentration as the quenching medium for quenching treatment;

[0034] 3) Cool to room temperature, wash the quenched parts with clean water, and then temper them at 590-610℃ for 2-4h;

[0035] 4) Take out the steel sample and air cool it to room temperature;

[0036] The water-based quenching liquid solution is prepared from a water-based quenching liquid composition, including the following components:

[0037]

[0038] Wherein, the polyether A is prepared by emulsion polymerization of allyl polyoxyethylene ether with styrene, acrylic acid and acrylamide, and the process is as follows:

[0039] S1. Add allyl polyoxyethylene ether, styrene, acrylic acid and acrylamide into a reaction bottle and stir and mix evenly at room temperature;

[0040] S2, prepare an emulsifier aqueous solution, then add it to the reaction bottle in step S1, stir evenly and heat to 70-80°C;

[0041] S3, prepare an initiator aqueous solution, add it dropwise into the reaction bottle of step S2 during stirring, continue the reaction for 3-5 hours, and discharge the material after cooling.

[0042] The molar ratio of the allyl polyoxyethylene ether to styrene, acrylic acid and acrylamide is 1:80-100:20-40:10-20; the molecular weight of the allyl polyoxyethylene ether is 2400; the amount of the emulsifier and the initiator are 2% and 1% of the total weight of the monomers, respectively. By changing the molar ratio, polyether A1, polyether A2 and polyether A3 with molecular weights of 11200, 18400 and 23500 are obtained respectively.

[0043] The polyether B is prepared by reacting hydroxyethyl cellulose with diethanolamine as an initiator, and polymerizing with ethylene oxide and propylene oxide in the presence of a catalyst to obtain a cellulose-based block polyether, and the process is as follows:

[0044] 1) Hydroxyethyl cellulose (purchased from Ruichu Biotechnology, molecular weight 737) was dissolved in DMSO, and then five times the amount of dichlorothionyl was added, and stirred at 60-80°C to obtain chlorohydroxyethyl cellulose; then it was redissolved in DMSO, and 10 times the amount of diethanolamine was added, and the reaction was carried out at 80-100°C overnight to obtain diethanolamine cellulose;

[0045] 2) The prepared diethanolamine cellulose is put into a high-pressure reactor, a sodium methoxide methanol solution is added as a catalyst, and polymerization reaction is carried out with propylene oxide and ethylene oxide in sequence at 100-140° C. to prepare a cellulose-based block polyether.

[0046] The mass ratio of diethanolamine cellulose, propylene oxide and ethylene oxide is 0.05:3 to 5:1. By changing the ratio, polyether B1, polyether B2 and polyether B3 with molecular weights of 3700, 5400 and 7500 are obtained respectively.

[0047] The above water-based quenching liquid composition is mixed in a certain proportion to obtain the following specific embodiment.

[0048] Embodiment 1:

[0049] 25% polyether A1, 40% polyether B1, 3% triazine fungicide, 2% isononylamino hexanoic acid rust inhibitor, 1% silicone defoamer and 30% water.

[0050] Embodiment 2:

[0051] 25% polyether A2, 40% polyether B2, 3% triazine fungicide, 2% isononyl amide caproic acid rust inhibitor, 1% silicone defoamer and 30% water.

[0052] Embodiment 3:

[0053] 25% polyether A3, 40% polyether B3, 3% triazine fungicide, 2% isononyl amide caproic acid rust inhibitor, 1% silicone defoamer and 30% water.

[0054] Embodiment 4:

[0055] 25% polyether A2, 40% polyether B3, 3% triazine fungicide, 2% isononylamino hexanoic acid rust inhibitor, 1% silicone defoamer and 30% water.

[0056] Embodiment 5:

[0057] 22% polyether A2, 38% polyether B3, 3% triazine fungicide, 2% isononylamino hexanoic acid rust inhibitor, 0.5% silicone defoamer and 34.5% water.

[0058] After the quenching liquid of the above embodiments is prepared, its appearance is observed, and it has good dispersibility, no stratification after long-term storage, and is easy to dilute with water. When used, it is diluted with water to a dilution of 20-30% by weight. The following table shows the physical and chemical properties of the quenching liquid with a concentration of 20%.

[0059] Table 1

[0060] Maximum cooling rate ℃ / s 300℃ cooling rate℃ / s <![CDATA[Kinematic viscosity (40 °C) mm 2 / s]]> Example 1 179 25 35.2 Example 2 185 26 33.8 Example 3 188 23 36.4 Example 4 198 21 38.2 Example 5 194 23 37.5

[0061] During the quenching process, the maximum cooling rate is around 500°C. The cooling rate at this time is relatively high, which can quickly cool the surface of large steel structure workpieces. When the temperature drops to 300°C, the cooling rate can be reduced to around 25%, and quenching cracking caused by insufficient internal stress due to excessive cooling rate will not occur.

[0062] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A metal heat treatment process, characterized in that: The following steps are involved: 1) Heat the steel sample to 900-1000℃ and keep it warm for 2-4h to achieve austenitization; 2) Putting into a quenching system with a water-based quenching liquid solution of 20-30% mass concentration as the quenching medium for quenching treatment; 3) Cool to room temperature, wash the quenched parts with clean water, and then temper them at 590-610℃ for 2-4h; 4) Take out the steel sample and air cool it to room temperature; The water-based quenching liquid solution is prepared from a water-based quenching liquid composition, including the following components: Wherein, the polyether A is prepared by emulsion polymerization of allyl polyoxyethylene ether with styrene, acrylic acid and acrylamide; The polyether B is prepared by polymerizing hydroxyethyl cellulose with diethanolamine as an initiator, and then reacting with ethylene oxide and propylene oxide in the presence of a catalyst to obtain a cellulose-based block polyether.

2. The metal heat treatment process according to claim 1, characterized in that: The preparation process of the polyether A is as follows: S1. Add allyl polyoxyethylene ether, styrene, acrylic acid and acrylamide into a reaction bottle and stir and mix evenly at room temperature; S2, prepare an emulsifier aqueous solution, then add it to the reaction bottle in step S1, stir evenly and heat to 70-80°C; S3, prepare an initiator aqueous solution, add it dropwise into the reaction bottle of step S2 during stirring, continue the reaction for 3-5 hours, and discharge the material after cooling.

3. The metal heat treatment process according to claim 1, characterized in that: The molar ratio of the allyl polyoxyethylene ether to styrene, acrylic acid and acrylamide is 1:80-100:20-40:10-20; the molecular weight of the allyl polyoxyethylene ether is 1000-2400; the dosage of the emulsifier and the initiator is 2% and 0.5-2% of the total weight of the monomers respectively.

4. The metal heat treatment process according to claim 1, characterized in that: The emulsifier aqueous solution is prepared from sodium dodecylbenzene sulfonate and water; the initiator aqueous solution is prepared from potassium persulfate or ammonium persulfate and water.

5. The metal heat treatment process according to claim 1, characterized in that: The preparation process of the polyether B is as follows: 1) Hydroxyethyl cellulose is dissolved in DMSO, and then five times the amount of dichlorothionyl is added, and stirred at 60-80°C to obtain chlorohydroxyethyl cellulose; then it is redissolved in DMSO, 10 times the amount of diethanolamine is added, and the reaction is carried out at 80-100°C overnight to obtain diethanolamine cellulose; 2) The prepared diethanolamine cellulose is put into a high-pressure reactor, a sodium methoxide methanol solution is added as a catalyst, and polymerization reaction is carried out with propylene oxide and ethylene oxide in sequence at 100-140° C. to prepare a cellulose-based block polyether.

6. The metal heat treatment process according to claim 1, characterized in that: The mass ratio of the diethanolamine cellulose, propylene oxide and ethylene oxide is 0.05:3-5:

1.

7. The metal heat treatment process according to claim 1, characterized in that: The bactericide is triazine, methylenebismorpholine or dimethyloxazolidine.

8. The metal heat treatment process according to claim 1, characterized in that: The rust inhibitor is selected from one of boric acid, boric acid esters and isononylaminocaproic acid.

9. The metal heat treatment process according to claim 1, characterized in that: The defoaming agent is a silicon defoaming agent.